PETROPHYSICAL FEATURES OF MAIKOP SERIES OF THE CRIMEAN-BLACK SEA REGION - Vyzhva, S.; Mykhailov, V.; Onischuk, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the article is to assess the petrophysical properties of reservoir rocks of traditional and non-traditional sources of hydrocarbons in the Maikop series of the Crimean-Black Sea region. The article is based on our own experimental investigations conducted on the basis of the petrophysical laboratory of the Institute of Geology of the Taras Shevchenko National University of Kyiv. Petrophysical properties of the clay rocks of the Maikop series in NW part of the Black Sea shelf; the central part of the Crimean Peninsula; Kerch Peninsula; Kerch shelf of the Azov Sea; the northern section of the Azov Sea shelf; Near Kerch section of the Black Sea shelf, as well as traditional collectors (mainly limestone and sandstone) of NW part of the Black Sea shelf; the northern section of the Azov Sea shelf; Near Kerch section of the Black Sea shelf were studied. For the first time, a complex characterization of petrophysical properties of non-traditional clay reservoirs of the Maikop series is given, and their comparison with the petrophysical characteristics of traditional reservoirs is made. Unconventional reservoirs (clays, mudstones) are characterized by significant fluctuations of petrophysical parameters. That is clearly associated with varying degrees of sample jointing. Thus, the bulk density of argillaceous rocks of the Maikop series varies from 1313 to 2621 kg/m3 (average 1760 kg/m3) in dry samples, from 1728 to 2708 kg/m3 (average 2081 kg/m3) in samples saturated with kerosene and the apparent mineralogical density range – from 2434 to 3022 kg/m3 (average 2584 kg/m3). The coefficient of open porosity varies from 0,3 % to 31,7 % (average 19,6 %). Open porosity on nitrogen varies from 6,6 % to 38,1 % (average 25,7 %). Traditional reservoir rocks (sandstone, limestone) are characterized by high capacitive-filtration properties. Bulk density of sandstones and limestones of the Maikop series changes from 1986 to 2638 kg/m3 (average 2341 kg/m3) in dry samples, from 2175 to 2662 kg/m3 (average 2647 kg/m3) in samples saturated with kerosene. The apparent mineralogical density varies from 2474 to 2724 kg/m3 (average 2630 kg/m3). Open porosity varies from 0,7 % to 24,1 % (average 11,0 %) in core samples saturation by kerosene and from 0,8 % to 25,0 % (average 11,3 %) in core samples saturated with model layers solution (as NaCl). Open porosity on "nitrogen" varies from 1,5 % to 25,9 % (average 12,9 %).